The China-U.S. Trade War and Future Economic Relations - Lau, Lawrence J., 1944- (Book collections on Project MUSE., 2019)
The relation between China and the United States is arguably the most important bilateral relation in the world today. The U.S. and China are respectively the largest and the second largest economies in the world. They are also respectively the largest and the second largest trading nations in the world as well as each other's most important trading partner. If China and the U.S. work together as partners towards a common goal, many things are possible. However, there exist significant friction and potential conflict in their economic relations. The large and persistent U.S.-China bilateral trade deficit is one of the problems. It is essential to know the true state of the China-U.S. trade balance before effective solutions can be devised to narrow the trade surplus or deficit. The impacts and potential impacts of the 2018 trade war between China and the U.S. on the two economies are analysed and discussed. The longterm forces that underlie the economic relations between the two countries beyond the 2018 trade war are examined. In this connection, how a "new type of major-power relation" between the two countries can help to keep the competition friendly and avert a war between them is explored.